Vesicoureteral Reflux Detected on Post-void Image of 99m Tc MAG3 Renal Scintigraphy - Naureen Nizar; Akhtar Ahmed (World Journal of Nuclear Medicine)
99m Tc MAG3 scintigraphic scan is sensitive at depicting focal parenchymal abnormalities and can be used for the measurement of overall renal function. We experienced a 5-year-old boy presenting with bilateral flank fain, intermittent urinary stream and dysuria. On the post-void delayed image of 99m Tc MAG3 scintigraphic scan vesicoureteral reflux was detected in left non-functioning kidney, which was missed on voiding cystourethrography.